Nickel Extraction From Morowali Laterite Ore With a Mixture of Hydrochloric Acid (HCl) and Sulfuric Acid (H2SO4) - Fitriani Fitriani; Daud K. Walanda; Mery Napitupulu; Vanny M. A. Tiwow; Detris Poba (Universitas Tadulako, 2024)
The study aims to determine the effects of temperature, leaching time, and the acid chloride-acid sulphate mixture ratio on nickel extraction and to identify the optimal extraction conditions for nickel laterite using the Taguchi method. Samples of laterite used come from the local District of Bahodopi, District of Morowali, Province of Central Sulawesi. Quantitative analysis using Atomic Absorption Spectrophotometry (AAS) with the variables under study included temperature with a condition level of 30 oC, 60 oC, and 90 oC, a leaching time of 3 hours, 6 hours, and 12 hours, and a mixture ratio of 0.5 M and H2SO4 0.5 M 1: 1, 1: 2, and 2: 1. Results of the study showed the condition of optimum is obtained which is at a temperature of 90 oC, while leaching ratio of 6 hours and mixture of acid 1: 2 with average absorbance optimum obtained are 0.736, the average concentration optimum of 8.085 ppm and the recovery value of 2.32 %.